2012
DOI: 10.1002/ijc.27448
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia upregulates ovarian cancer invasiveness via the binding of HIF‐1α to a hypoxia‐induced, methylation‐free hypoxia response element of S100A4 gene

Abstract: Hypoxia is known to play important roles in the development and progression of tumors. We previously demonstrated that S100A4, a critical molecule for metastasis, was upregulated in ovarian cancer cells. Therefore, we examined the mechanisms of the upregulation of S100A4 expression in ovarian carcinoma cells, with particular attention paid to the effects of hypoxia. The expression levels of S100A4 were found to be correlated with the invasiveness of ovarian carcinoma cells in vitro and in vivo, and the upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 43 publications
3
61
0
Order By: Relevance
“…Consistently, a mechanistic relationship between S100A4 and the hypoxia-inducible factor-1a (HIF-1a) in ovarian cancer cells has elucidated [28]. Hypoxia or hypoxia mimicking cobalt chloride (CoCl(2)) enhanced S100A4 expression in cancer cells [28,29]. These data support our findings that the activation of the HIF-1a signaling may be involved in arecoline-induced S100A4 expression and oncogenicity of OSCC.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Consistently, a mechanistic relationship between S100A4 and the hypoxia-inducible factor-1a (HIF-1a) in ovarian cancer cells has elucidated [28]. Hypoxia or hypoxia mimicking cobalt chloride (CoCl(2)) enhanced S100A4 expression in cancer cells [28,29]. These data support our findings that the activation of the HIF-1a signaling may be involved in arecoline-induced S100A4 expression and oncogenicity of OSCC.…”
Section: Discussionsupporting
confidence: 78%
“…In this study, CAY10585 (HIF1a inhibitor) was found to reduce S100A4 protein expression by arecoline in OE cells. Consistently, a mechanistic relationship between S100A4 and the hypoxia-inducible factor-1a (HIF-1a) in ovarian cancer cells has elucidated [28]. Hypoxia or hypoxia mimicking cobalt chloride (CoCl(2)) enhanced S100A4 expression in cancer cells [28,29].…”
Section: Discussionmentioning
confidence: 97%
“…The different responses to hypoxia between the two cell lines were also observed in some researches. 39,40 The phenomenon may be owing to some unknown differences in the two cell lines, such as the methylation of hypoxia-response elements of the gene. 39 The production of 5-HETE and LTB4 were higher under the hypoxia condition than normoxia.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 The phenomenon may be owing to some unknown differences in the two cell lines, such as the methylation of hypoxia-response elements of the gene. 39 The production of 5-HETE and LTB4 were higher under the hypoxia condition than normoxia. Interestingly, the production of 5-HETE and LTB4 were also significantly increased under the normoxia condition.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α has been associated with poor prognosis in a range of cancers including uterine, breast, and non-small cell lung cancer, as well as poor response to cancer therapies (Horiuchi et al, 2012;Kuo et al, 2012;Marton et al, 2012). Little is known, however, about the role of HIF-2α in solid tumors.…”
Section: Introductionmentioning
confidence: 99%